Advanced training enhances readiness to return to sport after anterior cruciate ligament reconstruction. Issue 1 (18th May 2021) - Meierbachtol, Adam; Obermeier, Michael; Yungtum, William; Bottoms, John; Paur, Eric; Nelson, Bradley J.; Tompkins, Marc; Chmielewski, Terese L.
Abstract: Patients with anterior cruciate ligament reconstruction (ACLR) are often psychologically and physically under‐prepared for sports participation. This study compared readiness to return to sport based on completion of advanced training after ACLR. Patients with ACLR who self‐selected participation in a 6‐week group‐format advanced training program (TRAINING) were compared to age‐ and sex‐matched patients who did not participate (NoTRAINING). Each group had 23 participants (14 females). Advanced training consisted of plyometric, strengthening, and agility exercises. Baseline and follow‐up testing included psychological measures (Anterior Cruciate Ligament Return to Sport after Injury [ACL‐RSI]; Tampa Scale for Kinesiophobia [TSK‐11]; Knee Activity Self‐Efficacy [KASE]; and fear intensity for the primary fear‐evoking task or situation) and a hop test battery. Return to sport criteria were ACL‐RSI score ≥70 points and limb symmetry index ≥90% on all hop tests. At follow‐up, KASE score was higher in TRAINING than NoTRAINING (92.7 vs. 89.1 points; respectively), but ACL‐RSI, TSK‐11 and fear intensity scores were not significantly different between groups. Return to sport criteria passing rate was not significantly different between groups at baseline (TRAINING: 13%, NoTRAINING: 30%) or follow‐up (TRAINING: 52%, NoTRAINING: 43%); however, the distribution of criteria met at follow‐up differed with more patients in TRAINING than NoTRAINING meeting hop test criteria (30% vs. 4%, respectively) and more patients in NoTRAINING than TRAINING failing to meet any criteria (25% vs. 0%, respectively). Advanced training after ACLR facilitated readiness for sport participation by improving confidence and hop performance, but may not have a preferential effect on fear.